Molecular surveillance of sandfly-borne phleboviruses in Robat Karim County, Tehran - Ebrahim Abbasi (Environmental Challenges)
Papatasi fever, also known as three-day fever, is a viral illness transmitted by the sandfly species Phlebotomus papatasi, characterized by symptoms similar to influenza. This study focused on Robat Karim County in Tehran Province, a region where climate change and the high prevalence of sandflies create an ideal environment for transmitting this virus. Researchers conducted a molecular survey of the Sandfly fever Sicilian virus (SFSV) in sandflies from seven selected areas within the county. A total of 679 sandflies were collected using traps and aspirators, with 500 samples randomly selected for analysis at the Medical Entomology Department. These samples were examined at the Tehran Pasteur Institute using real-time PCR to detect the presence of the Papatasi virus. The results showed no positive cases of the virus among the samples tested. Despite the absence of current infections, the study underscores the importance of preventive measures due to the conducive conditions for sandfly proliferation driven by climate change and the lack of a vaccine for sandfly fever. Efforts to control sandfly populations and reduce the risk of disease transmission remain critical in this region.